2009
DOI: 10.1177/1049732309355289
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Complex Needs of the Health Care Team: Identification of Nurse—Team Communication Practices Perceived to Enhance Patient Outcomes

Abstract: Nurses occupy a central position in today's increasingly collaborative health care teams that place a premium on quality patient care. In this study we examined critical team processes and identified specific nurse-team communication practices that were perceived by team members to enhance patient outcomes. Fifty patient-care team members were interviewed to uncover forms of nurse communication perceived to improve team performance. Using a grounded theory approach and constant comparative analysis, study find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
12

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 29 publications
2
68
0
12
Order By: Relevance
“…The results of this study also indicated that nurses were a part of a team of several healthcare professionals and their contribution to patient-centered care, while at the same time they overlooked basic services, as observed in the account that prioritized the catheter insertion when providing for the patient's needs. In addition, studies show nurses are recognized as agents of convergence and distribution of information (21) , who have power in interprofessional relations (6) . Complementariness of actions was identified in the accounts related to the interprofessional team and the team restricted to nursing professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also indicated that nurses were a part of a team of several healthcare professionals and their contribution to patient-centered care, while at the same time they overlooked basic services, as observed in the account that prioritized the catheter insertion when providing for the patient's needs. In addition, studies show nurses are recognized as agents of convergence and distribution of information (21) , who have power in interprofessional relations (6) . Complementariness of actions was identified in the accounts related to the interprofessional team and the team restricted to nursing professionals.…”
Section: Discussionmentioning
confidence: 99%
“…daily patient-nurse communication, both formal and informal [4,5]. Despite considerable efforts to ensure that the patient's information needs are met before hospital discharge, several studies claim that this goal is not reached [2,3,6,7].…”
mentioning
confidence: 99%
“…19 Interdisciplinarity exists not only in the interaction among workers through sharing knowledge and possibilities of intervention, but also through sharing responsibility to improve quality of care delivery and patient safety. 20 Even though the work at Nasf was reported to be the most favorable to interdisciplinary work through matrix support in team meetings and shared actions, its implementation is still a source of doubt and concern on the part of the Nasf workers themselves, 21 as the interdisciplinary practice needs to be increased. 22 Even though the work at Nasf drives workers to perform their practice based on interdisciplinarity, the reports show a lack of clarity and reiterates a dilemma between what is specific to each profession and what is generally from the field of health and, therefore, can be shared, such as concerns regarding boundaries of practice and potential loss of professional identity.…”
Section: Discussionmentioning
confidence: 99%